2020
DOI: 10.1177/0268355520921357
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicenter study on long-term complications of peripherally inserted central catheters positioned by electrocardiographic technique

Abstract: Background The intracavitary electrocardiogram (IC-ECG) method has been used for the tip location of central venous access devices for the advantage of being safe, accurate and highly cost effective. However, long-term follow-up is rare. This randomized clinical trial aimed to evaluate the long-term complications of peripherally inserted central catheters (PICCs) positioned by the IC-ECG method. Methods We randomized 2250 patients who needed PICC placement to either a landmark length estimation supplemented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…However, either they compared devices other than PICCs or they were quasiexperimental. Our results showed that both techniques had high technical success rates; consistent with the 91.7% demonstrated in a previous study [20]. There was no significant difference in T1/T2/T3 categories between groups.…”
Section: Discussionsupporting
confidence: 92%
“…However, either they compared devices other than PICCs or they were quasiexperimental. Our results showed that both techniques had high technical success rates; consistent with the 91.7% demonstrated in a previous study [20]. There was no significant difference in T1/T2/T3 categories between groups.…”
Section: Discussionsupporting
confidence: 92%
“…What precision can be reached under ECG is a frequent subject of controversy between users who are more for the use of FX technology or more for the use of ECG technology (2,3,28). What is undeniable is that ECG is clearly superior to blind insertion techniques (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Las principales medidas implantadas derivadas del proyecto flebitis Zero, ya reconocidas en otros estudios, son el uso de solución hidroalcohólica para la realización de la higiene de manos en vez del jabón neutro [20][21][22][23] , la desinfección de la zona de punción con clorhexidina alcohólica al 2% frente a otros antisépticos como la povidona yodada o el alcohol al 70% [8][9][10][11][12]23 y el empleo de apósito de fijación totalmente reforzado para la fijación del dispositivo. Estas medidas son determinantes de la IA de flebitis 11,26 .…”
Section: Or (Ic95%) P-valorunclassified
“…Los estudios relacionan estos factores con la presencia de catéteres venosos centrales de acceso periférico (CVCAP o PICC) 4,5 . Sin embargo, aun siendo la prevalencia ponderada de flebitis en los catéteres venosos periféricos (CVP) objetivamente superior que en los PICC (5,6-21,3% vs 1,25%) [5][6][7][8][9][10][11] , los principales factores de riesgo vinculados a la flebitis en los CVP no están del todo claros. Distintos estudios han identificado un foco multicausal integrado por elementos como la duración de la estancia hospitalaria 8,12,13 , la patología o proceso del paciente 14 , el número de catéteres insertados 9,15 , el tamaño del catéter canalizado 8 , el lugar de inserción 16 , la duración del mismo 13 , el tipo de fármaco administrado 6 , y la experiencia y formación del profesional sanitario implicado en su canalización y cuidado 17 .…”
Section: Introductionunclassified